Physical nature of size effects in TiAlNiAu/GaN ohmic contacts to AlGaN/GaN heteroepitaxial structures - Torkhov, Nikolay A.; Gradoboev, Alexandr V.; Orlova, K. N.; Toropov, A. S. (Semiconductor science and technology)
The size effect observed in TiAlNiAu/GaN ohmic contacts (OCs) makes itself evident in the dependence of their relative electrical characteristics R (SH) , R (SK) , rho and geometrical parameter L (T) on the LTLM test line width W-k . The paper explores the geometry of relief (topography) irregularities and their interface conductivity, indicating the great significance of the fractal geometry for the description of the electrophysical and device characteristics. The regularities discovered can be of great practical importance in terms of OC development and optimization for micro-/nanoelectronics demands.